Identification of Groenlandia densa (L.) Fourr. (Potamogetonaceae) as a New Genus and Species For The Flora of Iraq - Abdullah Sardar (مجلة التربية والعلم)
During the field trips to collect plant specimens, an aquatic plant was found in Gali-Sherana, near Deraluk (north-east Duhok) of Iraq. After the identification, it appeared that it belonged to the genus Groenlandia Gay and the species G. densa (L.) Fourr., and after reviewing all the available references involving the plant lists of Al-Rawi with Ridda and Daood and Flora of Iraq, the plant G. densa (L.) Fourr is considered a new genus and species added to the Flora of Iraq within the Potamogetonaceae family, collected from Gali-Sherana, near Deraluk (north-east of Duhok) in Mountainous Amadiya District (MAM). The features of G. densa are Rhizomatous aquatic perennial herbs; leaves submerged, opposite or sometimes in whorls of 3, somewhat recurved, acute-obtuse, margin undulate and minutely denticulate; inflorescence shortly pedunculate emergent spike, flowers 2-3 in a single inflorescence, anthers sessile, carpels 4, free. The identification of the specimens was done by helping the keys in the existing references involving Flora of Turkey, Flora Iranica, and Flora Europaea; vegetative and reproductive parts were described and reinforced by clarified photos. Pollen grain characteristics, such as color, shape, size, number, and surface configurations, have been mentioned, along with photos for polar and equatorial views. The map of Iraq has also been used to clarify the collection region, which is monotypic.